Preparation method and application of PtNi modified ZnO catalyst

By modifying ZnO with Pt and Ni, the light absorption range is broadened, the photogenerated carrier separation and transfer efficiency is improved and the surface reaction rate is accelerated, and the application limitation of a single ZnO photocatalyst in the benzylamine N-formylation reaction involving photocatalytic carbon dioxide is solved, and an efficient photocatalytic effect is achieved.

CN119869554AActive Publication Date: 2025-04-25TIANJIN UNIV

Patent Information

Application Number
CN202510085119.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The narrow light absorption range of a single ZnO photocatalyst, fast photogenerated carrier recombination and slow surface reactions limit its application in benzylamine N-formylation reactions involving photocatalytic carbon dioxide.

Method used

By introducing two metals with appropriate proportions of Pt and Ni to modify ZnO, the light absorption range of ZnO is broadened, the photogenerated carrier separation and transfer efficiency is improved, and the surface reaction rate is accelerated. The specific steps include hydrothermal synthesis of NiO-ZnO precursor, impregnation method, and reducing PtNi modified ZnO catalyst in combination with hydrogen gas.

Benefits of technology

Under room temperature and normal pressure visible light irradiation, the PtNi/ZnOx catalyst exhibits high-efficiency catalytic performance in the benzylamine N-formylation reaction involving photocatalytic carbon dioxide. The yield of amide products can reach 6 times that of single ZnO, the conversion rate of benzylamine substrate can reach 85.0%, the selectivity of amide products can reach 99.4%, and it has good cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869554A_ABST
    Figure CN119869554A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a PtNi modified ZnO catalyst. The preparation method comprises the following steps: stirring Zn (NO3) 2.6 H2O, Ni (NO3) 2.6 H2O and CO (NH2) 2 in deionized water to form a mixed solution, transferring the mixed solution into a high-pressure kettle, carrying out hydrothermal reaction, washing and drying to obtain a precursor; calcining the precursor in the air to obtain NiO-ZnO; a H2PtCl6 solution is dropwise added to the surface of NiO-ZnO, dipping is performed at the room temperature, a NaBH4 solution is added, stirring, washing and drying are performed at the room temperature, Pt / NiO-ZnO is obtained, the Pt / NiO-ZnO is placed in a reducing atmosphere to be calcined, and the PtNi modified ZnO catalyst PtNi / ZnOx is obtained. The catalyst is applied to a benzylamine N-formylation reaction in which carbon dioxide participates, the conversion rate of a benzylamine substrate can reach 85.0%, and the selectivity of amide products can reach 99.4%. The preparation process is simple to operate, and has better large-scale industrial production potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic organic synthesis, and in particular to a preparation method and application of a PtNi-modified ZnO catalyst. Background Art

[0002] The excessive carbon dioxide emitted by the rapid consumption of large amounts of fossil fuels poses a huge threat to the environment, causing a series of serious problems including the greenhouse effect and global climate change. Using carbon dioxide as a raw material to produce high-value-added chemicals is widely considered to be an effective solution to reduce carbon dioxide emissions and achieve sustainable development. Among the many efficient carbon dioxide conversion pathways, the N-formylation reaction of amines with the participation of carbon dioxide has attracted close attention due to the large-scale application of amide products in the fields of drug synthesis and industrial solvents. However, due to the structural stability of carbon dioxide itself, its activation and reduction processes are very difficult. At present, the N-formylation reaction of amines with the participation of carbon dioxide is mostly achieved by thermal catalysis, which usually requires relatively harsh reaction conditions. Compared with traditional thermal catalysis methods that require harsh reaction conditions, the N-formylation reaction of amines with the participation of photocatalytic carbon dioxide provides a more energy-saving and environmentally friendly method for converting carbon dioxide into high-value-added amide products.

[0003] ZnO has attracted much attention in the field of photocatalytic carbon dioxide conversion due to its suitable energy band structure and moderate carbon dioxide adsorption capacity. However, the narrow light absorption range of single ZnO, fast recombination of photogenerated carriers and slow surface reaction limit its further application. Therefore, how to broaden the light absorption range of ZnO, improve the photogenerated carrier separation efficiency of ZnO, and accelerate the surface reaction rate of ZnO is a technical problem that needs to be solved in this field. In order to overcome these problems, the commonly used technical means at present mainly include element doping, heterostructure construction, dye sensitization and co-catalyst loading. Among them, co-catalyst loading has been proved to be an effective method to improve the photogenerated carrier separation efficiency and accelerate the surface reaction rate while broadening the light absorption range of the catalyst. As a non-precious metal with abundant reserves, Ni is often used as a co-catalyst to improve the photogenerated carrier separation efficiency of various photocatalysts due to its good conductivity. At the same time, Ni nanoparticles also have the ability to induce plasma resonance effect, which can greatly improve the light response ability of the catalyst. By loading precious metal co-catalysts such as Pt on the surface of the photocatalyst, a large number of electron traps and active sites can be provided for the photocatalytic reaction, accelerating the surface reaction rate of the catalyst. Summary of the invention

[0004] In order to overcome the technical difficulties of narrow light absorption range, fast recombination of photogenerated carriers and slow surface reaction of single ZnO, the present invention provides a PtNi-modified ZnO catalyst and a preparation method thereof, and applies the catalyst to the photocatalytic carbon dioxide-involved N-formylation reaction of benzylamine. By modifying ZnO with Pt and Ni, the light absorption range of ZnO is broadened, the separation and transfer efficiency of photogenerated carriers of ZnO is improved, and the surface reaction rate of ZnO is accelerated, and an efficient photocatalytic carbon dioxide-involved N-formylation reaction of benzylamine is achieved under visible light irradiation at room temperature and normal pressure.

[0005] One of the purposes of the present invention is to provide a method for preparing a PtNi-modified ZnO catalyst, the specific steps of which are as follows:

[0006] (1) Stirring Zn(NO3)2·6H2O, Ni(NO3)2·6H2O and CO(NH2)2 in deionized water at room temperature until they are completely dissolved to obtain a mixed solution, transferring the mixed solution to an autoclave, subjecting it to a hydrothermal reaction, washing and drying it to obtain a precursor;

[0007] (2) calcining the precursor obtained in step 1) in air to obtain NiO-ZnO;

[0008] (3) adding H2PtCl6 solution dropwise to the surface of NiO-ZnO, immersing for 0.5-1h at room temperature, adding NaBH4 solution, stirring for 2-4h at room temperature, washing and drying to obtain Pt / NiO-ZnO;

[0009] (4) Placing Pt / NiO-ZnO in a reducing atmosphere for calcination to obtain a PtNi-modified ZnO catalyst PtNi / ZnO x .

[0010] In the step (1), the concentration of Zn(NO3)2·6H2O is 0.2-0.3 mol / L, the molar ratio of Zn(NO3)2·6H2O to Ni(NO3)2·6H2O is 2-4:1; and the molar ratio of CO(NH2)2 to total metal nitrates is 4-6:1.

[0011] In the step (1), the hydrothermal reaction temperature is 140-200° C., and the hydrothermal reaction time is 1-3 h.

[0012] In the step (2), the calcination temperature is 300-500° C. and the calcination time is 1-3 hours.

[0013] In the step (3), the H2PtCl6 solution is an ethanol solution of H2PtCl6 with a concentration of 8-10 mg / mL, and the Pt in the solution is 0.5%-1.5% of the total mass of NiO-ZnO; the NaBH4 solution is an aqueous solution of NaBH4 with a concentration of 0.07-0.08 mol / L, and the volume ratio of the NaBH4 solution to the H2PtCl6 solution is 40-50:1.

[0014] In the step (4), the reducing atmosphere is a mixture of hydrogen and nitrogen, wherein the volume ratio of hydrogen to nitrogen is 0.5-2:1.

[0015] In the step (4), the calcination temperature is 300-500° C. and the calcination time is 3-5 hours.

[0016] The catalyst prepared by the preparation method of the PtNi modified ZnO catalyst of the invention has a Ni content of 15%-25% of the total mass of the catalyst and a Pt content of 0.5%-1.5% of the total mass of the catalyst.

[0017] The catalyst PtNi / ZnO prepared according to the method x The reactant benzylamine and the solvent N,N-dimethylformamide were added to an autoclave reactor with a light window, and carbon dioxide was charged into the autoclave and the pressure was maintained at 0.1 MPa. A 300W xenon lamp with a 420nm filter was used to irradiate the sample at room temperature (light intensity was 350mW / cm 2 ) to react.

[0018] The amounts of catalyst, reactants and solvent added during the reaction are all conventional values ​​in the art. Catalyst PtNi / ZnO x The amount of PtNi / ZnO added is 10-50 mg, the amount of benzylamine added is 1-2 mmol, and the amount of N,N-dimethylformamide added is 5-10 mL. x The yield of amide products on PtNi / ZnO can reach 6 times that of single ZnO; after 24h of reaction, x The conversion rate of benzylamine substrate on PtNi / ZnO can reach 85.0%, and the selectivity of amide products can reach 99.4%. x The catalyst also has good cyclic stability.

[0019] The beneficial effects achieved by the present invention are:

[0020] (1) The present invention further optimizes the band structure of ZnO, enhances the light response ability of ZnO, improves the separation and transfer efficiency of photogenerated carriers of ZnO, and accelerates the surface reaction rate of ZnO by introducing two metals, Pt and Ni, in a suitable ratio to modify ZnO, thus breaking the limitations of the application of ZnO in the field of photocatalytic carbon dioxide-involved benzylamine N-formylation reaction. When the reaction is carried out under the same conditions, PtNi / ZnO x The yield of amide products on PtNi / ZnO can reach 6 times that of single ZnO; after 24h of reaction, x The conversion rate of benzylamine substrate on PtNi / ZnO can reach 85.0%, and the selectivity of amide products can reach 99.4%. x The catalyst also has good cyclic stability.

[0021] (2) PtNi / ZnO provided by the present invention x The catalyst is prepared by using a hydrothermal method to synthesize a NiO-ZnO precursor, and then adopting an impregnation method to load Pt and combine it with hydrogen reduction. This preparation process is simple to operate, has a high yield, is highly repeatable, and has good potential for large-scale industrial production.

[0022] (3) The present invention realizes an efficient photocatalytic N-formylation reaction of benzylamine with the participation of carbon dioxide under visible light irradiation at room temperature and normal pressure. Compared with traditional thermal catalytic methods, the reaction conditions are milder, which greatly reduces the reaction energy consumption and production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO x X-ray diffraction pattern (XRD) of the sample;

[0024] Figure 2 Pt1Ni prepared in Example 1 20 / ZnO x Transmission electron microscopy (TEM) images of the samples;

[0025] Figure 3 The ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO x UV-visible absorption spectrum (a) and steady-state fluorescence spectrum (b) of the sample;

[0026] Figure 4 The ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO xElectrochemical impedance spectroscopy (a) and transient photocurrent response curve (b) of the sample;

[0027] Figure 5 Pt1Ni prepared in Example 1 20 / ZnO x The catalytic performance of the sample as the reaction time increases (a), Pt1Ni prepared in Example 1 20 / ZnO x Cyclic stability test diagram of the sample (b) and Pt1Ni prepared in Example 1 before and after the cyclic test 20 / ZnO x XRD comparison diagram of samples (c);

[0028] Figure 6 The PtNi / ZnO prepared for the ZnO samples and Examples 1-5 x Photocatalytic performance of the samples. DETAILED DESCRIPTION

[0029] In order to make the contents of the present invention easier to understand, the present invention is further described below in conjunction with specific embodiments. The specific embodiments given are only for the purpose of enabling those skilled in the art to better understand the present invention, and do not limit the present invention in any form.

[0030] The materials, reagents, etc. involved in the following examples are all conventional raw materials in the art, and can be obtained from commercial channels unless otherwise specified. The experimental methods involved in the following examples are all conventional methods in the art, and can be carried out according to the techniques and conditions provided in the literature in the art or the product instructions unless otherwise specified.

[0031] Example 1

[0032] The synthesis of PtNi-modified ZnO catalyst is as follows:

[0033] (1) Weigh 2.558g Zn(NO3)2·6H2O and 0.867g Ni(NO3)2·6H2O in a beaker, add 40mL deionized water, and stir at room temperature for 0.5h. After the metal salt is completely dissolved, add 3.480g CO(NH2)2 and continue stirring at room temperature for 0.5h. After the CO(NH2)2 is completely dissolved, transfer the mixed solution to a 100mL autoclave and perform a hydrothermal reaction at 160℃ for 2h. After the autoclave is cooled to room temperature, rinse the obtained precipitate with deionized water and ethanol three times respectively, put it in an oven, and dry it at 70℃ for 12h to obtain the precursor.

[0034] (2) The dried precursor is placed in a muffle furnace, heated to 400°C at a rate of 5°C / min and kept at this temperature for 2 hours to obtain NiO-ZnO.

[0035] (3) Weigh 0.3g NiO-ZnO into a beaker, add 0.645mL of 10mg / mL H2PtCl6 ethanol solution, and soak at room temperature for 0.5h. After the soaking, slowly add 30mL of 0.075mol / L NaBH4 aqueous solution into the beaker and stir at room temperature for 2h. Rinse the obtained precipitate with deionized water and ethanol three times respectively, put it into a vacuum drying oven, and dry it at 60℃ for 12h to obtain Pt1 / NiO-ZnO.

[0036] (4) Weigh 0.3 g of Pt1 / NiO-ZnO and place it in a tube furnace. Pass a mixture of hydrogen and nitrogen with a volume ratio of 1:1 at a rate of 80 mL / min. Heat to 400 °C at a rate of 5 °C / min and keep warm for 4 h. After the tube furnace cools to room temperature, pass nitrogen at a rate of 40 mL / min for 0.5 h to obtain Pt1Ni 20 / ZnO x .

[0037] Figure 1 The ZnO sample and the Pt1Ni prepared in Example 1 are given. 20 / ZnO x XRD pattern of the sample. From the XRD pattern of the ZnO sample, it can be seen that it has a hexagonal structure (JCPDS No.36-1451). 20 / ZnO x In addition to the characteristic peaks of the ZnO phase, the XRD pattern of the sample also showed the peaks of the Ni (JCPDS No.04-0850) phase, proving the successful modification of Ni. 20 / ZnO x No characteristic peaks of Pt were observed in the XRD patterns of the samples, which is usually due to its low loading and high dispersion.

[0038] Figure 2 The Pt1Ni prepared in Example 1 is given 20 / ZnO x TEM image of the sample. Figure 2 (a) It can be seen that the sample is flaky as a whole. Figure 2 In (b), lattice fringes with spacings of 0.235, 0.205, and 0.284 nm were observed, corresponding to the Pt (111), Ni (111), and ZnO (100) crystal planes, respectively, which further proves the successful modification of Pt and Ni. Figure 2 (c) The STEM image and EDX element distribution spectrum show that Pt and Ni are 20 / ZnO xEvenly distributed in the sample.

[0039] Figure 3 (a) shows the ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO x UV-visible absorption spectrum of the sample. As can be seen from the figure, the modification of ZnO by Pt and Ni metals significantly improves the sample's ability to respond to light, especially the response to visible light. Figure 3 (b) shows the ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO x Steady-state fluorescence spectrum of the sample. Generally speaking, the weaker the intensity of the corresponding peak in the steady-state fluorescence spectrum of the sample, the weaker the recombination of the photogenerated electrons and photogenerated holes, which means that the photogenerated carrier separation ability of the sample is stronger. As can be seen from the figure, the modification of ZnO by Pt and Ni metals significantly reduces the fluorescence intensity of the sample, indicating that the modification of the two metals can greatly improve the overall photogenerated carrier separation efficiency of the sample.

[0040] Figure 4 (a) shows the ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO x Electrochemical impedance spectrum of the sample. As can be seen from the figure, the modification of ZnO by Pt and Ni metals significantly reduced the surface resistance of the sample and improved the transfer efficiency of photogenerated carriers on the sample surface, which is consistent with Figure 3 The fluorescence results are consistent with those of (b). Figure 4 (b) shows the ZnO sample and the Pt1Ni prepared in Example 1 20 / ZnO x Transient photocurrent response curve of the sample. As can be seen from the figure, the modification of ZnO by Pt and Ni metals significantly increased the surface photocurrent intensity of the sample, which once again proves that the modification of ZnO by Pt and Ni metals can improve the separation and transfer efficiency of photogenerated carriers on the sample surface.

[0041] Example 2

[0042] The synthesis of PtNi-modified ZnO catalyst is as follows:

[0043] (1) Weigh 2.380g Zn(NO3)2·6H2O and 0.569g Ni(NO3)2·6H2O in a beaker, add 40mL deionized water, and stir at room temperature for 0.5h. After the metal salt is completely dissolved, add 3.588g CO(NH2)2 and continue stirring at room temperature for 0.5h. After the CO(NH2)2 is completely dissolved, transfer the mixed solution to a 100mL autoclave and perform a hydrothermal reaction at 140℃ for 3h. After the autoclave is cooled to room temperature, rinse the obtained precipitate with deionized water and ethanol three times respectively, put it in an oven, and dry it at 70℃ for 12h to obtain the precursor.

[0044] (2) The dried precursor was placed in a muffle furnace, heated to 300°C at a rate of 5°C / min and kept at that temperature for 3h to obtain NiO-ZnO (Ni 15 ).

[0045] (3) Weigh 0.3 g NiO-ZnO (Ni 15 ) in a beaker, add 0.645mL of 10mg / mL H2PtCl6 ethanol solution, and soak at room temperature for 1h. After the immersion is completed, slowly add 30mL of 0.075mol / L NaBH4 aqueous solution to the beaker and stir at room temperature for 3h. The obtained precipitate is rinsed with deionized water and ethanol three times respectively, and then placed in a vacuum drying oven and dried at 60℃ for 12h to obtain Pt1 / NiO-ZnO(Ni 15 ).

[0046] (4) Weigh 0.3 g Pt1 / NiO-ZnO(Ni 15 ) was placed in a tube furnace, and a mixture of hydrogen and nitrogen with a volume ratio of 0.5:1 was introduced at a rate of 90 mL / min, and the temperature was raised to 300°C at a rate of 5°C / min and kept at this temperature for 5 h. After the tube furnace was cooled to room temperature, nitrogen was introduced at a rate of 60 mL / min and continued to be purged for 0.5 h to obtain Pt1Ni 15 / ZnO x .

[0047] Example 3

[0048] The synthesis of PtNi-modified ZnO catalyst is as follows:

[0049] (1) Weigh 3.570g Zn(NO3)2·6H2O and 1.613g Ni(NO3)2·6H2O in a beaker, add 40mL deionized water, and stir at room temperature for 0.5h. After the metal salt is completely dissolved, add 4.216g CO(NH2)2 and continue to stir at room temperature for 0.5h. After the CO(NH2)2 is completely dissolved, transfer the mixed solution to a 100mL autoclave and perform a hydrothermal reaction at 160℃ for 2h. After the autoclave is cooled to room temperature, rinse the obtained precipitate with deionized water and ethanol three times respectively, put it in an oven, and dry it at 70℃ for 12h to obtain the precursor.

[0050] (2) The dried precursor was placed in a muffle furnace, heated to 400°C at a rate of 5°C / min and kept at that temperature for 2h to obtain NiO-ZnO (Ni 25 ).

[0051] (3) Weigh 0.3 g NiO-ZnO (Ni 25 ) in a beaker, add 0.645mL of 10mg / mL H2PtCl6 ethanol solution, and soak at room temperature for 0.5h. After the immersion is completed, slowly add 30mL of 0.075mol / L NaBH4 aqueous solution to the beaker and stir at room temperature for 4h. The obtained precipitate is rinsed with deionized water and ethanol three times respectively, and then placed in a vacuum drying oven and dried at 60℃ for 12h to obtain Pt1 / NiO-ZnO(Ni 25 ).

[0052] (4) Weigh 0.3 g Pt1 / NiO-ZnO(Ni 25 ) was placed in a tube furnace, and a mixture of hydrogen and nitrogen with a volume ratio of 2:1 was introduced at a rate of 90 mL / min, and the temperature was raised to 400°C at a rate of 5°C / min and kept at that temperature for 4 hours. After the tube furnace was cooled to room temperature, nitrogen was introduced at a rate of 30 mL / min and continued to be purged for 0.5 hours to obtain Pt1Ni 25 / ZnO x .

[0053] Example 4

[0054] The synthesis of PtNi-modified ZnO catalyst is as follows:

[0055] (1) Weigh 2.558g Zn(NO3)2·6H2O and 0.867g Ni(NO3)2·6H2O in a beaker, add 40mL deionized water, and stir at room temperature for 0.5h. After the metal salt is completely dissolved, add 3.480g CO(NH2)2 and continue to stir at room temperature for 0.5h. After the CO(NH2)2 is completely dissolved, transfer the mixed solution to a 100mL autoclave and perform a hydrothermal reaction at 180℃ for 2h. After the autoclave is cooled to room temperature, rinse the obtained precipitate with deionized water and ethanol three times respectively, put it in an oven, and dry it at 70℃ for 12h to obtain the precursor.

[0056] (2) The dried precursor is placed in a muffle furnace, heated to 400°C at a rate of 5°C / min and kept at this temperature for 2 hours to obtain NiO-ZnO.

[0057] (3) Weigh 0.3g NiO-ZnO into a beaker, add 0.400mL of 8mg / mL H2PtCl6 ethanol solution, and soak at room temperature for 0.5h. After the soaking is completed, slowly add 20mL of 0.07mol / L NaBH4 aqueous solution into the beaker and stir at room temperature for 3h. Rinse the obtained precipitate with deionized water and ethanol three times respectively, put it into a vacuum drying oven, and dry it at 60℃ for 12h to obtain Pt 0.5 / NiO-ZnO.

[0058] (4) Weigh 0.3 g Pt 0.5 / NiO-ZnO was placed in a tube furnace, and a mixture of hydrogen and nitrogen with a volume ratio of 1:1 was introduced at a rate of 80 mL / min. The temperature was raised to 400°C at a rate of 5°C / min and then kept at that temperature for 4 hours. After the tube furnace was cooled to room temperature, nitrogen was introduced at a rate of 40 mL / min and continued to be purged for 0.5 hours to obtain Pt 0.5 Ni 20 / ZnO x .

[0059] Example 5

[0060] The synthesis of PtNi-modified ZnO catalyst is as follows:

[0061] (1) Weigh 2.558g Zn(NO3)2·6H2O and 0.867g Ni(NO3)2·6H2O in a beaker, add 40mL deionized water, and stir at room temperature for 0.5h. After the metal salt is completely dissolved, add 3.480g CO(NH2)2 and continue to stir at room temperature for 0.5h. After the CO(NH2)2 is completely dissolved, transfer the mixed solution to a 100mL autoclave and perform a hydrothermal reaction at 200℃ for 1h. After the autoclave is cooled to room temperature, rinse the obtained precipitate with deionized water and ethanol three times respectively, put it in an oven, and dry it at 70℃ for 12h to obtain the precursor.

[0062] (2) The dried precursor was placed in a muffle furnace, heated to 500°C at a rate of 5°C / min and kept at that temperature for 1 hour to obtain NiO-ZnO.

[0063] (3) Weigh 0.3g NiO-ZnO into a beaker, add 1.065mL of 9mg / mL H2PtCl6 ethanol solution, and soak at room temperature for 1h. After the soaking is completed, slowly add 40mL of 0.08mol / L NaBH4 aqueous solution into the beaker and stir at room temperature for 4h. Rinse the obtained precipitate with deionized water and ethanol three times respectively, put it into a vacuum drying oven, and dry it at 60℃ for 12h to obtain Pt 1.5 / NiO-ZnO.

[0064] (4) Weigh 0.3 g Pt 1.5 / NiO-ZnO was placed in a tube furnace, and a mixture of hydrogen and nitrogen with a volume ratio of 1:1 was introduced at a rate of 80 mL / min, and the temperature was raised to 500°C at a rate of 5°C / min and then kept at this temperature for 3 h. After the tube furnace was cooled to room temperature, nitrogen was introduced at a rate of 40 mL / min and continued to be purged for 0.5 h to obtain Pt 1.5 Ni 20 / ZnO x .

[0065] Example 6

[0066] Catalyst photocatalytic reaction performance test.

[0067] 50 mg of Pt1Ni prepared in Example 1 20 / ZnO x The sample, 2 mmol benzylamine and 10 mL N,N-dimethylformamide were added to an 80 mL autoclave reactor with a light window. 0.2 MPa of carbon dioxide was filled into the autoclave and then vented (this process was repeated 10 times to remove other gases in the autoclave before the reaction). Finally, the carbon dioxide pressure in the autoclave was maintained at 0.1 MPa and irradiated with a 300 W xenon lamp with a 420 nm filter at room temperature (light intensity of 350 mW / cm 2) to react. After the reaction, Pt1Ni 20 / ZnO x Separation of sample and product, Pt1Ni 20 / ZnO x The sample was rinsed three times with deionized water and ethanol respectively, placed in a vacuum drying oven, and dried at 60°C for 12 h for cyclic testing; the product was diluted and fixed to volume, and then characterized by gas chromatography-mass spectrometry (GC-Agilent6890A, MS-Agilent 5973C) and gas chromatograph (Nexis GC-2030).

[0068] Figure 5 (a) shows the Pt1Ni prepared in Example 1 20 / ZnO x The catalytic performance of the sample as the reaction time increases. It can be seen from the figure that when Pt1Ni 20 / ZnO x When the sample is used as a catalyst, as the reaction time increases, the conversion rate of the substrate benzylamine gradually increases while the selectivity of the amide products remains basically unchanged. After the reaction reaches 24 hours, the conversion rate of the substrate benzylamine can reach 85.0%, and the selectivity of the amide products can reach 99.4%. Figure 5 (b) shows the Pt1Ni prepared in Example 1 20 / ZnO x The cyclic stability test diagram of the sample. It can be seen from the figure that after multiple cycles of testing, its performance has not decreased significantly, proving that Pt1Ni 20 / ZnO x The samples have good stability. Figure 5 (c) shows the Pt1Ni prepared in Example 1 20 / ZnO x The XRD comparison diagram of the sample before and after multiple cycles of testing shows that the crystal structure of the sample has not changed significantly after multiple cycles of testing, which further proves that Pt1Ni 20 / ZnO x The samples have good stability.

[0069] Example 7

[0070] Catalyst photocatalytic reaction performance test.

[0071] 10 mg of PtNi / ZnO prepared in Example 1-5 was added xThe sample, 1 mmol benzylamine and 5 mL N,N-dimethylformamide were added to an 80 mL autoclave reactor with a light window. 0.2 MPa of carbon dioxide was filled into the autoclave and then vented (this process was repeated 10 times to remove other gases in the autoclave before the reaction). Finally, the carbon dioxide pressure in the autoclave was maintained at 0.1 MPa and irradiated with a 300 W xenon lamp with a 420 nm filter at room temperature (light intensity of 350 mW / cm 2 ) to react. After the reaction, the PtNi / ZnO x The sample was separated from the product, and the product was characterized by gas chromatography-mass spectrometry (GC-Agilent 6890A, MS-Agilent 5973C) and gas chromatograph (Nexis GC-2030) after being diluted to a fixed volume.

[0072] Figure 6 The ZnO samples and PtNi / ZnO prepared in Examples 1-5 are given. x Photocatalytic performance of the sample. As can be seen from the figure, after 6 hours of reaction under visible light irradiation (λ>420nm) at room temperature and atmospheric pressure, the performance of the ZnO sample is poor, the conversion rate of the substrate benzylamine is only 7.5%, and the selectivity of the amide product is 95.8%. After the ZnO is modified with Pt and Ni, the catalytic activity of the sample is significantly improved. When Pt1Ni 20 / ZnO x When the sample is used as a catalyst, the conversion rate of benzylamine substrate can reach 46.4%, and the selectivity of amide products can reach 99.2%.

[0073] The several specific implementations described above are only for the purpose of enabling those skilled in the art to better understand and implement the present invention, but do not limit the present invention in any form. Those skilled in the art may make other different forms of changes or modifications based on the above description, and the changes or modifications derived therefrom that do not deviate from the principles of the present invention or the claims are still within the scope of protection of the present invention.

Claims

1. A method for preparing a PtNi-modified ZnO catalyst, characterized in that: The following steps are involved: (1) Stirring Zn(NO3)2·6H2O, Ni(NO3)2·6H2O and CO(NH2)2 in deionized water at room temperature until they are completely dissolved to obtain a mixed solution, transferring the mixed solution to an autoclave, subjecting it to a hydrothermal reaction, washing and drying it to obtain a precursor; (2) calcining the precursor obtained in step 1) in air to obtain NiO-ZnO; (3) adding H2PtCl6 solution dropwise to the surface of NiO-ZnO, immersing for 0.5-1h at room temperature, adding NaBH4 solution, stirring for 2-4h at room temperature, washing and drying to obtain Pt / NiO-ZnO; (4) Placing Pt / NiO-ZnO in a reducing atmosphere for calcination to obtain a PtNi-modified ZnO catalyst PtNi / ZnO x .

2. The method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: In step (1), the concentration of Zn(NO3)2·6H2O is 0.2-0.3 mol / L, the molar ratio of Zn(NO3)2·6H2O to Ni(NO3)2·6H2O is 2-4:1; and the molar ratio of CO(NH2)2 to total metal nitrates is 4-6:

1.

3. The method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is 140-200° C., and the hydrothermal reaction time is 1-3 h.

4. The method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: In step (2), the calcination temperature is 300-500° C. and the calcination time is 1-3 h.

5. The method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: In step (3), the H2PtCl6 solution is an ethanol solution of H2PtCl6 with a concentration of 8-10 mg / mL, and the Pt in the solution is 0.5%-1.5% of the total mass of NiO-ZnO; the NaBH4 solution is an aqueous solution of NaBH4 with a concentration of 0.07-0.08 mol / L, and the volume ratio of the NaBH4 solution to the H2PtCl6 solution is 40-50:

1.

6. The method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: In step (4), the reducing atmosphere is a mixture of hydrogen and nitrogen, wherein the volume ratio of hydrogen to nitrogen is 0.5-2:

1.

7. The method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: In step (4), the calcination temperature is 300-500° C. and the calcination time is 3-5 hours.

8. The catalyst prepared by the method for preparing a PtNi-modified ZnO catalyst according to claim 1, characterized in that: The Ni content of the PtNi-modified ZnO catalyst is 15%-25% of the total mass of the catalyst, and the Pt content is 0.5%-1.5% of the total mass of the catalyst.

9. Use of the PtNi-modified ZnO catalyst according to claim 8 in the photocatalytic N-formylation reaction of benzylamine with the participation of carbon dioxide.

Citation Information

Patent Citations

  • Preparation method of nano porous Ni-Fe alloy catalyst

    CN110813296A

  • Preparation method and application of catalyst

    CN113398937A

  • Bimetal oxide nano material and preparation method and application thereof

    CN115722229A

  • Carbon doped tin disulphide and methods for synthesizing the same

    US20180280942A1

  • Nanometal oxide Adsorbents for Desulfurization of Hydrocarbon Fuels

    US20200188873A1

Cited By

  • Porous carbon supported copper catalyst as well as preparation method and application thereof

    CN122124835A